An integrative systems biology view of host-pathogen interactions: The regulation of immunity and homeostasis is concomitant, flexible, and smart - Grossman, Zvi; Meyerhans, Andreas; Bocharov, Gennady (Frontiers in Immunology, 2023)
The systemic organization of humans and other mammals is essentially “preprogrammed”, and the basic interacting units – the cells – can be roughly mapped into discrete sets of developmental lineages and maturation states. However, focusing on the immune system, we and others invoked evidence – now overwhelming – suggesting dynamic acquisition of cellular properties and functions, through tuning, re-networking, chromatin remodeling, and adaptive differentiation. The genetically encoded “algorithms” that govern the integration of signals and the computation of new states are not fully understood but are believed to be “smart”, designed to enable the cells and the system to discriminate meaningful perturbations from each other and from “noise”. Cellular sensory and response properties are shaped in part by recurring temporal patterns, or features, of the signaling environment. We compared this to associative brain learning. Learning enables multilevel regulation to be geared to performance: we showed that imposed higher-level selection, guided by feedback from both the tissue itself and the neural system, allows tunable immune cells to progressively coordinate their response to injury or infection with that of other cell types across tissues and organs. This in turn is comparable to supervised brain learning. Consequently, resident or recruited antigen-specific and innate immune cells can eradicate a pathogen while simultaneously sustaining functional homeostasis. Fortunately, much of the “training” that a living system requires to function in the face of disturbances is already incorporated into its design, so it does not need to deep-learn how to face a new challenge each time from scratch. Instead, the system is only required to learn from experience how to re-select a built-in strategy, or a combination, and can then use tuning to refine its organization and responses. We cite recent efforts to identify such strategies and characterize pathology. One proposed strategy is boosting the flux of uninfected cells into and throughout an infected tissue to rinse and replace the infected cells. Finally, since immunologic memories are imprinted both systemically and within the targeted tissues, it is desirable to incorporate attenuated-pathogen vaccines and informed choice of immunomodulators in vaccination schemes to enhance tissue preparedness.